Consumer loyalty in Indonesia’s Fast-Food Industry a systematic literature review of service quality price fairness satisfaction and word of mouth in the digital era - Hadi, Seno Sudarmono; Widyastuti, Sri; Darmansyah, Darmansyah (Journal of Economics and Business Letters, 2025)
This study conducts a systematic literature review to synthesize and critically evaluate empirical evidence on the determinants of consumer loyalty in Indonesia’s fast-food industry. Drawing on 31 peer-reviewed studies published between 2010 and 2025, the review explores the roles of service quality, price fairness, consumer satisfaction, and word-of-mouth (WOM) in shaping loyalty outcomes. Following PRISMA guidelines, relevant literature was systematically identified, screened, and appraised across major academic databases, with inclusion criteria focused on empirical research conducted in the Indonesian fast-food context. The synthesis confirms that service quality and satisfaction are consistently strong predictors of loyalty, while the effects of price fairness are more context-dependent and often mediated through value perceptions and WOM. The review identifies critical research gaps, including the insufficient integration of digital service attributes into service quality frameworks, limited modeling of WOM as a mediator and moderator, and the lack of comparative analyses between local and international brands. Future research directions are proposed, emphasizing the need for omnichannel conceptualizations, longitudinal and experimental designs, and greater attention to e-WOM and platform-mediated pricing dynamics. The findings offer actionable insights for managers and marketers in Indonesia’s fast-food sector to enhance customer engagement strategies in an increasingly competitive and digitalized market.